2020
DOI: 10.30595/medisains.v18i1.6940
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of the elderly: a comparison between community-dwelling elderly and in social welfare institutions

Abstract: Background: Quality of life (QoL) among the elderly is a neglected issue, especially in developing countries, including Indonesia. The QoL of the elderly is dependent on four domains. Living arrangements play an important role in determining QoL.Objective: The present study aimed to compare the differences in QoL among community-dwelling elderly and in social welfare institutions.Methods: This was a cross-sectional study. Participants were sampled from two settings: social welfare institutions and the communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The trend at the European level is to move from an institutional care system to a system that provides care for older people in a more familiar environment, i.e., at home. Existing studies have found that older people enjoy a higher quality of life if they remain in their home receiving the care they need than if they live in a residential care institution [ 22 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…The trend at the European level is to move from an institutional care system to a system that provides care for older people in a more familiar environment, i.e., at home. Existing studies have found that older people enjoy a higher quality of life if they remain in their home receiving the care they need than if they live in a residential care institution [ 22 , 35 , 36 , 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a study conducted in Brazil reported that the quality of life (QoL) of older persons living in longterm care facilities is lower than those living in the community because they were older and experienced worse socioeconomic and health conditions (Vitorino et al, 2013). Similarly, Kiik and Nuwa (2020) research indicated that Indonesian elderlies living in community-dwelling experience higher QoL than those residing in welfare institutions. Moreover, Su and Wang (2019) found that elderlies residing in community-based home care in Guangzhou city generally showed better QoL than institutional care.…”
Section: Introductionmentioning
confidence: 99%
“…This factor is a natural factor that is usually experienced by the elderly, it cannot be changed because it is a destiny that must be lived. The inhibiting factors encountered in religious development in nursing homes were in the form of monotonous delivery of material, declining physical condition of the elderly, and communication barriers 6. 5.…”
mentioning
confidence: 99%